Health outcomes after acute ischemic stroke:retrospective and survival analysis from Oman - Abdullah M. Al Alawi; Ikhlas Al Busaidi; Emaad Al Shibli; Al-Reem Al-Senaidi; Shahd Al Manwari; Ibtisam Al Busaidi; Fatema Muhanna; Ahmed Al Qassabi (Annals of Saudi Medicine)
BACKGROUND: Stroke mortality and related functional disability have been declining over the last two decades, but stroke continues to represent the second leading cause of cardiovascular death worldwide and the number one cause for acquired long-term disability. OBJECTIVES: Assess short- and long-term health outcomes after acute ischemic stroke and analyze factors associated with poor survival and functional outcomes. DESIGN: Retrospective and survival analysis SETTING: Inpatient unit at a tertiary care referral hospital. PATIENTS AND METHODS: All patients admitted with acute ischemic stroke from 1 January 2017 to 31 August 2018 were included in the study. Functional status was assessed using the modified Rankin Scale (mRS). Other demographic and clinical variables were obtained from medical records. Data were analyzed by multivariable logistic regression, Cox proportional hazards, and the Kaplan-Meier method. Long-term follow-up data, including mortality and mRS was collected by follow-up phone call. MAIN OUTCOME MEASURES: Functional dependency and factors associated with mortality. SAMPLE SIZE AND CHARACTERISTICS: 110 with mean age of 67.0 (14.7) years; 59 patients (53.6%) were males. RESULTS: Hypertension (75.5%), diabetes mellitus (54.6%), and dyslipidemia (29.1%) were common. Sixty-five patients (59.1%) had mRS >2 upon discharge including 18 patients (16.4%) who died during the hospital stay. The cumulative mortality rate was 25.4% (28/110) at 12 months and 30.0% (33/110) at 24 months. Twenty-nine stroke survivors (29/70, 41.4%) remained physically dependent (mRS >2) at the end of follow-up. Old age, atrial fibrillation, history of prior stroke, chronic kidney disease, and peripheral arterial disease were associated with increased mortality and functional dependence. CONCLUSIONS: Patients in Oman with acute ischemic stroke tend to have a high comorbidity burden, and their functional dependency and mortality are higher compared to patients from developed countries. Therefore, evidence-based measures such as establishing stroke units are essential to improve the health outcomes of patients with acute ischemic stroke. LIMITATIONS: Retrospective at single center. CONFLICT OF INTEREST: None.